Dzieła warsztatu Korneckich dla małopolskich cystersów .......... 333 - Kluz, Paulina (Dzieje i kultura Cystersów w Polsce, 2025)
WORKS OF THE KORNECKI WORKSHOP FOR THE CISTERCIANS OF MAŁOPOLSKABetween 1748 and 1776-1778 there was a carpentry-sculpting and painting workshop in Gdów run by the Kornecki family. The master of this workshop was sculptor and painter Piotr, with whom worked his half-brother Stanisław, his sons Antoni, Ignacy, Jan and Stanisław, as well as his collaborators Franciszek Kozicki, Piotr Małecki and his pupil Franciszek Jaworski. Kornecki’s workshop in Gdów fulfilled the need for church furnishings in a comprehensive way, as he was carrying out orders for altar structures and pulpits, sculptural and ornamental decoration and altar paintings. During this period, from the late 1740s and for the whole third quarter of the 18th century, I have established that he completed numerous works in several places. Among them were also works for Cistercians of Małopolska in Szczyrzyc and Mogiła (now Kraków). Many stylistic similarities, and even the same formal and compositional solutions applied in works by the Kornecki family can be recognized in the Cistercian works being analyzed, making it possible to attribute these to their workshop. The first order of the Kornecki family for the Cistercians was probably to make two side altars and a pulpit for the abbey church in Szczyrzyc during the years 1766-1768. It had an impact on subsequent  orders also in Mogiła (now Kraków). In the 1770s (before 1776-1778) the workshop made an altar of St. Anthony with two paintings (an unidentified Cistercian saint – missing, Mother of God with Child and St. John the Baptist), which was originally located on the eastern wall of the southern transept of the Cistercian church in Mogiła. The retable was removed in 1945 during the restoration of the church and is now presented as the main altar in the Church of Our Lady of the Snows in Tokarnia. Around 1776 the Kornecki’s workshop also made the furnishings for the wooden church of St. Bartholomew in Mogiła, which was under the care of the Cistercians, which included three side altars with paintings (St. Casimir, St. Isidor, St. Ludgard) and perhaps an illusionistic painted main altar. It was possible to establish the believed origin of the artistic methods used in the described works, which is leaning favorably towards the works of artists from the artistic center in Kraków, and also shows the wide use of engravings.